Understanding gen z's online self-presentation on multiple Instagram accounts - Yoanita, Desi; Chertian, Vivian Graciela; Ayudia, Putu Dinda (Jurnal Studi Komunikasi, 2022)
Currently, Instagram has become one of the most effective mediums for personal branding. Interestingly, celebrities or influencers are not the only ones using it. Gen Z also uses Instagram to present their image as ideal as possible. However, that does not mean they lose their true identity. This generation prefers to have multiple Instagram accounts to express themselves. This study aimed to explore why Gen Z had multiple Instagram accounts, how they chose the followers, and how they conducted online self-disclosure through content categorisation of each account. Through this study, the researchers wished to contribute a deeper understanding of the cyber-self, particularly in communication. A focused group discussion was conducted with 21 adolescents aged 18-20 who live in Java, Bali, Kalimantan, and Sulawesi with varying family backgrounds, education, occupation, and gender. The study found that Gen Z distinguished their account based on the designation they have for each account, what self-aspect they want to display, and it finally affects how they disclose information on Instagram.